Harnessing Artificial Intelligence in Healthcare and Petroleum Industries Advances in Fraud Detection and Novel Approaches in Cancer Medicine - George Edison (CV. Multi Kreasi Media, 2024)
This review explores the transformative role of artificial intelligence (AI) in enhancing sustainability and operational efficiency in the healthcare and petroleum industries. It highlights the potential of AI technologies to revolutionize patient care through improved diagnostics, personalized medicine, and optimized resource allocation in healthcare, while also addressing critical ethical considerations such as data privacy, algorithmic bias, and accountability. In the petroleum sector, AI applications in resource extraction, predictive maintenance, and emissions monitoring present significant opportunities for reducing environmental impact and increasing operational efficiency. The review emphasizes the necessity of establishing ethical frameworks and regulatory standards to navigate the complexities associated with AI deployment, ensuring that its benefits are distributed equitably across diverse populations. Furthermore, it underscores the importance of collaboration among stakeholders, including policymakers, industry leaders, and ethicists, to promote responsible AI usage that prioritizes sustainability and equity. By harnessing AI's capabilities thoughtfully, both sectors can advance toward a more efficient, equitable, and sustainable future while addressing the pressing challenges of our time.